Global poverty and inequality: are the revised estimates open to an alternative interpretation?. Issue 3 (4th March 2018) - Edward, Peter; Sumner, Andy
Abstract: The level of, and trends in, global inequality and global poverty are indicative assessments of who has benefited from economic growth. The revision of price data has led to a reassessment of those estimates. Through an extensive overview of the implications, we argue that the data can be read in different ways. Official estimates show global extreme poverty and global inequality are considerably lower than previously thought. We argue that these changes are much less significant than they at first appear, and we present a more nuanced alternative interpretation by exploring changes across the entire global distribution.